A Validation Study of the Revised Diagnostic Criteria from the International Workshop on Ocular Sarcoidosis at a Single Institute in Japan. (17th November 2021) - Handa-Miyauchi, Mari; Takase, Hiroshi; Tanaka, Miyuki; Akiyama, Masako; Ohno-Matsui, Kyoko; Mochizuki, Manabu
ABSTRACT: Purpose : To validate the revised criteria of the International Workshop on Ocular Sarcoidosis (IWOS) for the diagnosis of ocular sarcoidosis (OS). Methods : A retrospective chart review study was performed on 323 patients including 51 patients with biopsy-proven sarcoidosis and 272 patients with other uveitis entities. Data on intraocular signs and systemic investigations were collected, and sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and the Youden index were calculated. Results : All intraocular signs and most systemic investigations showed high diagnostic parameters. Sensitivity, specificity, PPV, and NPV of the revised IWOS criteria were 1.000, 0.930, 0.728, and 1.000, respectively. Presumed or probable OS showed lower sensitivity and higher specificity when compared with the best Youden index. Conclusion : The revised IWOS criteria are useful in Japanese patients, but could possibly be improved by modifying the criterion of presumed or probable OS.